Outcome of Asphyxiated Term Newborns in Relation to the Time of Referral to a Tertiary Care Hospital - Tariq Saeed, Rubina Zulfiqar, Mohammad Ahsan Afzal, Tariq Mahmood Raja, Muhammad Zahoor ul Haq (Journal of Rawalpindi Medical College, 2012)
Background:To determine the outcome of asphyxiated term newborns in relation with the time of referral to a tertiary care unit. Methods: In this descriptive study,142 newborns with birth asphyxia were grouped into Group A and B depending upon the referral duration i.e., less than 24 hours and 24-48 hours respectively. Demographic details, age, gender, weight, duration of birth asphyxia, maternal age, parity, mode, place of delivery, delivery conducting personnel, hypoxic ischemic encephalopathy stage and outcome were documented. Results: Group A (referral time less than 24 hours) frequency was 33.8% and Group B (referral time 24 to 48 hours) was 66.2%.Maximum patients were delivered at hospital( 47.9%). Mortality was higher in home deliveries (69.2%) and was significantly higher in deliveries conducted by dais ( 70.8%) Hypoxic ischemic encephalopathy stage III was seen in 39.4% cases of Group B, while none were seen in Group A Conclusion: Aphyxiated newborns have a significant morbidity and mortality in association with delayed referral to a tertiary care hospital.